Crescimento de cafeeiros plantados em diferentes épocas com polímero hidro retentor - Oliveira, Luiz Paulo Vilela de (2014)
The productivity of coffee crops in Brazil is still very low. In field, we note that, among the reasons for low productivity in Brazilian crops, is the low rate of crop renewal. One of the reasons that most prevent crop renewal is the low initial productivity due to the climatic conditions that can be unfavorable in certain seasons and the lack of new technologies for the plantation. Therefore, the use of hydro retaining polymers in the implementation of non-irrigated crops can be a technique of the utmost importance for coffee culture. Allied to this, we believe that, anticipating the planting season to the initial months of the rainy season, we can achieve higher initial productivities. The experiment was installed at the Department of Agriculture of the Universidade Federal de Lavras, in Lavras, Minas Gerais, Brazil, in the period from October of 2012 to March 2013, using the design in randomized blocks, in a 6x2 factorial scheme, with three replicates, totalizing 12 treatments and 36 plots. The treatments were constructed by six planting seasons: October, November, December, January, February and March, using or not the hydro retaining polymer applied in the planting crypt in the dosage of 1.5 liters of previously diluted solution of 1.5 kg of hydro retaining polymer in 400 liters of water. The growth evaluations were performed in July of 2013 and January of 2014, evaluating the following traits: height of the plants, diameter of the stem, number of knots on the orthotropic branch, number of plagiotropic branches, length of the first plagiotropic branch, number of leaf pairs on the first plagiotropic branch and mortality. We verified that the hydro retaining polymer and its interaction with the planting season did not interfere with the analyzed parameters and the planting season interfered with all parameters measured, allowing the conclusion that anticipating the planting season favors the initial growth of the crop.